Cloud-Native Design Principles for Scalable Enterprise Systems - Vamsi Krishna Reddy Munnangi (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This article presents a comprehensive overview of cloud-native design principles for enterprise systems, focusing on the fundamental aspects that drive modern digital infrastructure transformation. It addresses the evolution from traditional architectures to cloud-native solutions, highlighting the critical components of microservices, containerization, and API-first development. The discussion encompasses essential patterns for managing stateless and stateful services, distributed data management strategies, and effective API gateway implementations. The article demonstrates how cloud-native architectures enhance system resilience, scalability, and maintainability through real-world implementation examples and performance metrics. The content illustrates the significance of proper service boundary design, state management techniques, and data consistency patterns in building robust enterprise applications. It also examines how API-first development and gateway patterns contribute to improved system integration and operational efficiency. The article also explores the organizational impact of cloud-native adoption, including cultural shifts in development practices and operational procedures. It provides insights into the practical considerations of implementing cloud-native architectures, addressing common challenges and success factors. The discussion extends to emerging trends and best practices in cloud-native computing, offering guidance for organizations embarking on their digital transformation journey.